Faktor-faktor yang Mempengaruhi Kinerja Karyawan Bagian Produksi CV. Bintang Rema Utama Purwokerto - Khoirul Zulfa; P. Edi Sumantri; Ratna Puji Astuti (Prosiding Seminar Nasional Ilmu Ekonomi dan Akuntansi, 2024)
This research aims to determine and analyze the influence of the physical work environment, job training, compensation and work discipline on the performance of CV employees. Bintang Rema Utama Purwokerto production department. The population in this study were all employees of CV. Bintang Rema Utama Purwokerto production section in November 2023 as many 149 people. The samples obtained were 109 using the probability sampling method with a sampling technique, namely simple random sampling technique. This research uses multiple linear regression analysis tools with the help of SPSS statistics 26 software. The results of this research show that the physical work environment, job training, compensation and work discipline have a positive and significant effect on the performance of CV employees. Bintang Rema Utama Purwokerto production department. The implication in this research is that there is more attention from CV leaders. Bintang Rema Utama Purwokerto strives to improve the performance of its employees, such as providing lighting, circulation and room humidity that supports it, providing training materials that are easy to understand, providing adequate benefits and facilities, and warning employees whose attendance is not on time.